Dip-coating deposition of resistive BiVO4 thin film and evaluation of their photoelectrochemical parameters under distinct sources illumination - da Silva, M. R. [UNESP]; Scalvi, L. V.A. [UNESP]; Neto, V. S.L.; Dall’Antonia, L. H. (Springer Nature, 2016)
Resistive monoclinic bismuth vanadate (BiVO4) nanocrystals in the form of thin films were obtained by the solution combustion synthesis coupled with the dip-coating deposition process. The structure, morphology, and optical properties of BiVO4 nanocrystals were characterized by means of x-ray diffraction (XRD), scanning electron microscopy (SEM), and UV-Vis spectroscopy. The photoelectrochemical properties were obtained by cyclic voltammetry and chronoamperometry techniques in potassium chloride (KCl) electrolyte solution under distinct visible light sources irradiation condition. Under blue InGaN light emitting diode (LED) irradiation, the electrode has a better efficiency, faster response time (260Â ms), and faster decay time (65Â ms), when compared with the irradiation by dichroic lamp. Besides, the photocurrent density (jph) is approximately 39 times higher than jph obtained under dichroic lamp. The performance analysis based on the methylene blue degradation reaction has shown that the BiVO4 material has higher electroactivity under InGaN LED irradiation condition, with estimated kobs value of 200Â Ã Â 10−4Â min−1, which is a little higher than the value obtained with dichroic lamp illumination. In the dark condition, the BiVO4 presented much lower photocatalytic activity.
Keywords: BiVO4; Dichroic lamp; InGaN LED; Resistive; Thin film